2013
DOI: 10.1186/1479-5876-11-169
|View full text |Cite
|
Sign up to set email alerts
|

Clear cell renal cell carcinoma associated microRNA expression signatures identified by an integrated bioinformatics analysis

Abstract: BackgroundClear cell renal cell carcinoma (ccRCC) represents the most invasive and common adult kidney neoplasm. Mounting evidence suggests that microRNAs (miRNAs) are important regulators of gene expression. But their function in tumourigenesis in this tumour type remains elusive. With the development of high throughput technologies such as microarrays and NGS, aberrant miRNA expression has been widely observed in ccRCC. Systematic and integrative analysis of multiple microRNA expression datasets may reveal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 46 publications
(50 reference statements)
0
52
0
Order By: Relevance
“…We first applied LSOSS to detect differentially expressed microRNAs and genes from the RNA-seq data. LSOSS generally outperforms the t -statistics and is more competent for cancer data analysis, as our previous studies indicated [22, 37]. Then the inverse expression pattern of miRNAs and genes was predicted by the spearman correlation.…”
Section: Discussionmentioning
confidence: 97%
“…We first applied LSOSS to detect differentially expressed microRNAs and genes from the RNA-seq data. LSOSS generally outperforms the t -statistics and is more competent for cancer data analysis, as our previous studies indicated [22, 37]. Then the inverse expression pattern of miRNAs and genes was predicted by the spearman correlation.…”
Section: Discussionmentioning
confidence: 97%
“…Molecularly, the tumour suppressor von Hippel-Lindau (VHL) is frequently inactivated by mutations (1), leading to increased proliferation, enhanced angiogenesis and de-differentiation of tumour cells. ccRCC pathogenesis is linked to abnormal regulation of certain microRNAs (miRNAs) (2,3). The latter are a class of ~22 nucleotide-long, single-stranded non-coding, nucleic acid molecules involved in the regulation of proliferation (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…According to the statistical evidences described in our previous work, miRNAs with larger NOD and TFP values were more likely to be candidate biomarkers and represented biomarker miRNAs that had strong abilities to regulate genes independently and, meanwhile, regulate more TF genes. The application of biomarker discovery for prostate cancer [23, 25], sepsis [26], clear cell renal cell carcinoma [27], and pediatric acute myeloid leukemia [24] demonstrated its great predictive power.…”
Section: Introductionmentioning
confidence: 99%